Quantification of several atmospheric gases from high resolution infrared solar spectra obtained at the South Pole in 1980 and 1986 - Goldman, Aaron; Murcray, Frank J.; Murcray, Frank H.; Murcray, David G.; Rinsland, Curtis P. (1988)
High-resolution solar absorption spectra recorded at the Amundsen-Scott South Pole Station were analyzed to obtain total column amounts of O3, N2O, HNO3, CO2, CH4, and CF2Cl2, and to investigate the differences in the values obtained in December 1980 with those obtained in December 1986. In addition, vertical column amounts for HCl, NO, NO2, and C2H6 were derived for December 1986. One interesting feature of these results is that the total column amounts of HCl measured for several days at the South Pole (/6.4 + or - 0.8/ x 10 to the 15th molecules/sq cm) were high compared with the HCl column amounts reported for lower latitudes.